Evaluation of a Validated Biomarker Test in Combination With a Symptom Index to Predict Ovarian Malignancy. Issue 2 (1st February 2017) - Urban, Renata R.; Smith, Alan; Agnew, Kathy; Bonato, Vinicius; Goff, Barbara A.
Abstract : Objective: This study aimed to evaluate the predictive ability of a multivariate biomarker test in combination with a symptom index (SI) to identify ovarian cancer in a cohort of women planning to undergo surgery for a pelvic mass. Methods: This was a prospective study of patients seen at a tertiary care medical center. Following consent, patients completed an SI and preoperative serum was collected for a Food and Drug Administration–cleared multivariate biomarker test [multivariate index assay (MIA)]. Results for the SI and MIA were correlated with operative findings and surgical pathology. Results: Of 218 patients enrolled, 124 (56.9%) had benign disease and 94 (43.1%) had borderline tumors or carcinomas. Sixty-six patients had a primary ovarian or fallopian tube cancer. The median age of patients enrolled in this study was 54 years (interquartile range, 44–63 years), of whom 148 (67.9%) were postmenopausal. More than a third (36.3%) of patients with benign masses was accurately identified as low risk by MIA and SI. The sensitivity and negative predictive value (NPV) of the SI relative to primary ovarian cancer was 87.9% (95% CI, 77.9%–93.7%) and 91.6% (95% CI, 84.3%–95.7%), respectively. The sensitivity and NPV of CA125 was 75.4% (95% CI, 63.7%–84.2%) and 86.4% (95% CI, 79.1%–91.5%), respectively, and the sensitivity and NPV of the MIA were 93.9% (95% CI, 85.4%–97.6%) and 94.5% (95% CI, 94.5%–100%), respectively. The overall sensitivity for the combination of MIA plus SI was 100% (66/66; 95% CI, 94.5%–100%), and specificity was 36.3% (45/124; 95% CI, 28.4%–45.0%), with an NPV of 100% (95% CI, 92.1%–100%). Conclusions: The addition of a patient-reported SI, which captures subjective symptoms in an objective manner, improved the sensitivity of MIA across all stages and subtypes of ovarian cancer.